Fretting fatigue performance and life prediction of 1120 aluminum alloy wires of overhead conductors. (October 2022) - Matos, I.M.; Araújo, J.A.; Castro, F.C.
Highlights: New fretting fatigue tests were performed on AA1120 wires. New fatigue tests were conducted on smooth and circumferentially V-notched AA1120 wires. Fatigue performances of AA1120 and traditional AA1350 and AA6201 were compared. AA1120 and AA6201 exhibited similar fretting fatigue resistance. Fretting fatigue lives were satisfactorily predicted by a nonlocal Smith-Watson-Topper criterion. Abstract: Aluminum alloy (AA) 1120 wires have increasingly been used in overhead conductors due to their high tensile and creep resistance and electrical conductivity compared to other aluminum alloys. However, few studies have been conducted to characterize the fatigue strength of this material, specially under fretting conditions. In this work, fretting fatigue tests are performed on AA1120 wires of an AAAC 823 MCM conductor. A tension test, and fatigue tests on smooth and circumferentially V-notched wires were also carried out. The experimental results are compared to test data from AA1350 and AA6201 wires. Under tension, the AA1120 displayed an intermediate ultimate tensile strength between the ones from the AA1350 and AA6201. For the same stress amplitudes, the AA1120 wires used in the axial fatigue tests had longer lives than the AA1350 wires but considerably shorter lives than the AA6201 wires. However, under fretting fatigue, both AA1120 and AA6201 wires had similar fatigue strengths. A nonlocal life prediction criterion was evaluated using the fretting fatigue data. Most of the life estimates were within a factor of 3 of the observed lives when the input stress field was obtained from an elastic-plastic contact model.